Development and evaluation of online menopause awareness training for line managers in UK organizations. (February 2019) - Hardy, Claire; Griffiths, Amanda; Hunter, Myra S.
Highlights: There are calls for managers and employers to have knowledge and awareness of the menopause to meet the needs of working women. This paper describes the development and evaluation of a brief, online menopause awareness training for managers. Results indicate that this may be a feasible and effective way to improve managers' awareness, knowledge and confidence in discussing menopause at work. Abstract: Objectives: To develop and evaluate a 30-min online training for managers, in order to improve menopause-related knowledge, attitudes and confidence in having supportive discussions with women experiencing menopausal symptoms at work. The study also explored intentions and behaviour in terms of having conversations. Study design: A prospective, pre-post design involved collecting data at three time points: pre-training, immediately after training, and four weeks post-training. Three UK organizations (one public, two private sector) participated. On-line questionnaires collected sociodemographic and background data. Qualitative and quantitative evaluation data were collected in post-intervention questionnaires. Paired t-tests and McNemar tests examined statistical differences pre- and post-training; thematic content analysis was performed on qualitative data. Main outcome measures: Menopause knowledge, attitudes and confidence in talking about the menopause at work, intentions, and actual behaviour. Results: 270 staff were invited and 98 consented to participate; 62 and 61 provided data immediately and 4 weeks post training, respectively. Compared to pre-training scores, statistically significant improvements were found in menopause-related knowledge, attitude (not viewing the menopause as an embarrassing topic to talk about at work), confidence in talking about the menopause with staff, and intentions to discuss menopause, at both follow-up assessments. Over 90% of respondents reported that they found the training useful and would recommend it to others. Conclusions: A brief menopause awareness training may be a feasible and effective way to help managers become more knowledgeable about menopause-related problems and more confident in discussing and exploring solutions with their staff.